Are orchid bees at risk? First comparative survey suggests declining populations of forest-dependent species - Nemésio,A (2013)
The two largest Atlantic Forest remnants in the state of Espírito Santo, eastern Brazil, namely ‘Reserva Biológica de Sooretama’ (REBIO Sooretama) and ‘Reserva Natural Vale’ (RNV), were surveyed for their orchid-bee faunas. Seventeen scent baits were used to attract orchid-bee males. Three-thousand, two hundred and twenty-five males belonging to 24 species were actively collected with insect nets during 100 hours in March, April and December, 2009. In comparison with a previous study in the same area twelve years before, it is evident that the abundance of all forest-dependent orchid bees analysed declined around 50%, and it was statistically significant (P = 0.022) for Euglossa marianae Nemésio, 2011, the most sensitive to anthropogenic disturbances of all Atlantic Forest orchid bees. On the other hand, the abundance of populations of species tolerant to open or disturbed areas rose. Possible explanations are discussed.